Trajetórias de pessoas trans no mercado formal de trabalho em João Pessoa -PB: entre a política, o estigma e a resistência - Melo, Luciana Carmelio Silva Rodrigues (2021)
This dissertation proposes to sociologically discuss the insertion in the formal Job market of trans people in the city of João Pessoa-PB, from the experience of employability in a call center company. Therefore, it seeks to reflect on the tensions between a precarious way of working, the telemarketing, a social inclusion policy for trans people, the Transcidadania Project, implemented by the LGBT Coordination of the João Pessoa City Hall (PMJP) and the expectations and experiences of the people involved in these processes, mainly trans people. In this study, we will use the term trans people to refer to those people who understand and identify themselves as transvestites, transsexuals, transgender or non-binary. In this sense, we will not deal properly with defined identities, but with the construction of a feminine or masculine becoming that individuals elaborate within themselves, with theoretical support from Queer Theory. The qualitative research was carried out through semi-structured interviews and bibliographical research.